Exploring the relationship between scientist human capital and firm performance: The case of biomedical academic entrepreneurs in the SBIR program - Dirk Czarnitzki; Andrew A. Toole (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
Do academic scientists bring valuable human capital to the companies they found or join? If so, what are the particular skills that compose their human capital and how are these skills related to firm performance? This paper examines these questions using a particular group of academic entrepreneurs – biomedical research scientists who choose to commercialize their knowledge through the U.S. Small Business Innovation Research Program. Our conceptual framework assumes the nature of an academic entrepreneurs? prior research reflects the development of their human capital. We highlight differences in firm performance that correlate with differences in the scientists? research orientations developed during their academic careers. We find that biomedical academic entrepreneurs with human capital oriented toward exploring scientific opportunities significantly improve their firms? performance of research tasks such as ?proof of concept? studies. Biomedical academic entrepreneurs with human capital oriented toward exploring commercial opportunities significantly improve their firms? performance of invention oriented tasks such as patenting. Consistent with prior evidence, there also appears to be a form of diminishing returns to scientifically oriented human capital in a commercialization environment. Holding the commercial orientation of the scientists? human capital constant, we find that increasing their human capital for identifying and exploring scientific opportunities significantly detracts from their firms? patenting performance.
Keywords: O32; D21; J24; L65; 330; Academic Entrepreneurship; SBIR Program; Human Capital; Biotechnology